What Got Lost in the Rabbit Hole? Translations of Alice's Adventures in Wonderland into Russian - Kaloh Vid, Natalia; Žagar-Šoštarić, Petra (2026)
Literary works are retranslated for a number of reasons, inclduing enhancing the quality of the earlier version, “refreshing” the language, bringing the reader closer to the source text, adapting the translation for a new and often more complete edition, removing differences and deviations from the earlier version, or adapting the text to changing norms of translation in the target society. The book focuses on twelve translations of Alice's Adventures in Wonderland into Russian (1909–2000), a unique case in the history of re-translations which offer a rich and prescious materail for a comparative study. A close textual analysis of the original and translations takes into consideration translations of culturally-specific elements, parodies, personal names, linguistic varities, historic references and other stylistic components. As the results of the analysis show, translations of children’s literature do not always and do not necessarily imply exclusively domestication with substitutions with a familiar concept from the target culture.
Keywords: literary translation; retranslation; Alice; English; Russian